Evaluación de las propiedades psicométricas de las escalas Epworth modificada para niños (ESS), cuestionario de sueño pediátrico (PSQ) y el cuestionario de calidad de vida (OSA-18) en pacientes pediátricos con sospecha de apnea obstructiva de sueño de la Fundación Neumológica Colombiana (2026)
Background: Pediatric obstructive sleep apnea (OSA) is a prevalent disorder with substantial clinical and functional impact. Diagnosis relies on polysomnography, a resource-intensive and limited-access test. In this context, clinical questionnaires are widely used to support evaluation; however, their psychometric performance and relative utility vary across populations and constructs. This study aimed to assess the validity, reliability, factorial structure, and reproducibility of the Epworth Sleepiness Scale modified for children (ESS), the Pediatric Sleep Questionnaire (PSQ), and the OSA18 in children with suspected OSA evaluated at the Fundación Neumológica Colombiana. Methods: We conducted an analytical cross-sectional observational study for scale validation, with consecutive recruitment between September 2024 and July 2025 at a tertiary referral center.